2020
DOI: 10.1038/s41467-020-15317-6
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic restoration of retinal ganglion cell activity in the living primate

Abstract: Optogenetic therapies for vision restoration aim to confer intrinsic light sensitivity to retinal ganglion cells when photoreceptors have degenerated and light sensitivity has been irreversibly lost. We combine adaptive optics ophthalmoscopy with calcium imaging to optically record optogenetically restored retinal ganglion cell activity in the fovea of the living primate. Recording from the intact eye of a living animal, we compare the patterns of activity evoked by the optogenetic actuator ChrimsonR with natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 24 publications
8
62
0
Order By: Relevance
“…Using ex vivo live imaging and histology, we show here that expression persists in cells in the perifovea region more than 20 months after the injection, and we demonstrate, with electrophysiological recordings, that these transduced RGCs remain functional, displaying rapid, robust responses. Previous studies based on ex vivo retinal recordings in NHP models have demonstrated efficient optogene expression for up to six months [11,13,14], and studies based on retinal imaging in vivo extended this functional window up to 14 months [17]. This maintenance of activity so long after the injection is consistent with the notion that gene therapy can lead to long-term gene expression.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Using ex vivo live imaging and histology, we show here that expression persists in cells in the perifovea region more than 20 months after the injection, and we demonstrate, with electrophysiological recordings, that these transduced RGCs remain functional, displaying rapid, robust responses. Previous studies based on ex vivo retinal recordings in NHP models have demonstrated efficient optogene expression for up to six months [11,13,14], and studies based on retinal imaging in vivo extended this functional window up to 14 months [17]. This maintenance of activity so long after the injection is consistent with the notion that gene therapy can lead to long-term gene expression.…”
Section: Discussionsupporting
confidence: 76%
“…We have previously shown that the transduced retina displays high spatiotemporal resolution ex vivo , compatible with the perception of highly dynamic visual scenes at light levels suitable for use in humans. Other studies have provided evidence of retinal activation in vivo [17]. Here, we demonstrate, in non-human primates, sustained functional efficacy ~20 months after delivery of an AAV2.7m8-ChrimsonR-tdTomato vector similar to that currently undergoing clinical evaluation.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Several pre-clinical optogenetic studies have used canine and non-human primate models to assess the safety and expression profile of optogenetic vectors (Ivanova et al, 2010;Sengupta et al, 2016;Ameline et al, 2017) as well as the function and characteristics of optogenetic tools in terms of their ability to restore vision (Chaffiol et al, 2017;McGregor et al, 2020). Compared to murine models, limited in vivo (Ivanova et al, 2010;Chaffiol et al, 2017;McGregor et al, 2020) and ex-vivo (Sengupta et al, 2016) transduction of retinal ganglion cells was demonstrated in marmoset and macaque retinae, respectively, following delivery of AAV encoding microbial opsin-based sensors, with intra-ocular inflammatory responses observed in treated eyes (Chaffiol et al, 2017). In addition, despite longterm expression, similar findings of limited expression were observed in a canine model following treatment with a microbial and a human opsin (Ameline et al, 2017).…”
Section: Large Animal Modelsmentioning
confidence: 99%
“…Dr. Juliette McGregor and Dr. William Merigan presented data from imaging studies in cynomolgus NHPs ( Macaca fascicularis ) that used adaptive optics to optically record from retinal ganglion cells following intravitreal injection of AAV2 vectors ( Table 1A ) for calcium imaging (GCaMP) optogenetic therapy (ChrimsonR). 15 Because inflammation would greatly limit imaging, macaques were both pre-screened to exclude animals with anti-AAV antibodies and pretreated with subcutaneous cyclosporine A for one to 20 weeks before AAV vector injection ( Table 2A ). Although numbers were small, increasing time of immunosuppressive pretreatment was generally associated with improved lateral extent of foveal gene expression.…”
Section: Lessons From Preclinical Animal Studies Of Ocular Gene Theramentioning
confidence: 99%